A study of manifestations of children's socio-emotional behavior with the introduction of pets in the curriculum - Perez, Ma. Karina A.; Villanueva Annavi Marie G.; Hizon, Evalyn G. (2011.)
This research was conducted to find out how classroom pets are integrated into the preschool curriculum. It sought to determine the manifestations of children's behavior when pets are introduced in he curriculum of younger and older age groups. A qualitative, descriptive study using naturalistic, non-participative observation was conducted in two classes of the University of the Philippines Child Development Center. Using purposive sampling, the classes qualified the selection criteria developed for the study. Event sampling forms were used to record the observed socio-emotional behaviors during the two-week observations. A behavior classification tool, with pre-determined behavior categories, aided the researchers in comparing the frequencies of the manifested behaviors. Interviews with each class' teachers were conducted to gather more data about the class, children's socio-emotional behaviors and development. Findings show that the inclusion of classroom pets in the curriculum made it richer, more interesting, and more developmentally-appropriate. The children have also manifested most favorably socio-emotional behaviors such as caring, sharing, helpfulness, curiosity and initiative. It also showed children's care and affection towards the classroom pets. HAving pets is beneficial to early childhood professionals and parents as they work together to attain an enriching learning environment for the child's optimum socio-emotional development.
Thesis (BSFLCD)--University of the Philippines Diliman.
Keywords: Children and animals; Child development -- Philippines